Pattern Authoring: Web Service Oriented Architecture (International Journal of Current Engineering and Technology, 2014)
Architecture to loosely coupled architecture. Reusability has been playing the important role in software process and tools development since last decade. Software industry is to achieve intense perfection in throughput and superiority because of reusability in development process. In this paper, I will going to discuss the guideline to pattern authoring for web services with loosely coupled architecture. This pattern will provide framework for creation of web service with highest amount of reusability.
Keywords: SOA: Service Oriented Architecture, WS: Web services, WSDL: Web Service Description/Definition Language, W-SOA: Web Service Oriented Architecture, ESB: Enterprise Service Bus, MQ: Messaging Queue.